Digital Governance and Privacy: Revisiting Legal Protections under Expanding Surveillance Systems - Clara Mendes; Rafaela Lima; Omar Khan (Yayasan Adra Karima Hubbi, 2026)
Background. The rapid advancement of digital surveillance technologies in the age of big data has raised significant concerns regarding privacy rights and state power. As governments and corporations increasingly rely on digital surveillance to enhance security and gather data, the implications for personal privacy have become more complex. Purpose. The study aims to assess the adequacy of current legal frameworks in balancing the demands of security with the protection of individual freedoms. Method. A qualitative methodology was employed, involving an analysis of international legal documents, case law, and expert interviews. Results. The findings indicate that existing laws, while addressing privacy to some extent, often lack enforceability and fail to effectively limit state surveillance powers. Conclusion. This study concludes that stronger, more adaptive legal frameworks are necessary to ensure privacy protection while accommodating legitimate state surveillance needs. The research contributes to the growing discourse on the intersection of law, technology, and human rights, offering recommendations for reforming legal safeguards in the digital age.